Sitagliptin and Roux-en-Y gastric bypass modulate insulin secretion via regulation of intra-islet PYY - Guida, C; McCulloch, L; Godazgar, M; Stephen, S; Baker, C; Basco, D; Dong, J; Chen, D; Clark, A; Ramracheya, R (John Wiley & Sons Ltd, 2017)
The gut hormone peptide tyrosine tyrosine (PYY) is critical for maintaining islet integrity and restoring islet function following Roux-en-Y gastric bypass (RYGB). The expression of PYY and its receptors (NPYRs) in islets has been documented but not fully characterized. Modulation of islet PYY by the proteolytic enzyme DPP-IV has not been investigated and the impact of DPP-IV inhibition on islet PYY function remains unexplored. Here we have addressed these gaps and their effects on glucose-stimulated insulin secretion (GSIS). We have also investigated changes in pancreatic PYY in diabetes and following RYGB.Immunohistochemistry and gene expression analysis were used to assess PYY, NPYRs and DPP-IV expression in rodent and human islets. DPP-IV activity inhibition was achieved by sitagliptin. Secretion studies were used to test PYY and sitagliptin effects on insulin release, and the involvement of GLP-1. Radioimmunoassays were used to measure hormone content in islets.PYY and DPP-IV localized in different cell types in islets while NPYRs expression was confined to the beta-cells. Chronic PYY application enhanced GSIS in rodent and diabetic human islets. DPP-IV inhibition by sitagliptin potentiated GSIS; this was mediated by locally-produced PYY, and not GLP-1. Pancreatic PYY was markedly reduced in diabetes. RYGB strongly increased islet PYY content, but did not lead to full restoration of pancreatic GLP-1 levels.Local regulation of pancreatic PYY, rather than GLP-1, by DPP-IV inhibition or RYGB can directly modulate the insulin secretory response to glucose, indicating a novel role of pancreatic PYY in diabetes and weight-loss surgery.